2008
DOI: 10.5194/acp-8-6199-2008
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ACE-FTS v2.2 measurements of HCl, HF, CCl<sub>3</sub>F and CCl<sub>2</sub>F<sub>2</sub> using space-, balloon- and ground-based instrument observations

Abstract: Abstract. Hydrogen chloride (HCl) and hydrogen fluoride (HF) are respectively the main chlorine and fluorine reservoirs in the Earth's stratosphere. Their buildup resulted from the intensive use of man-made halogenated source gases, in particular CFC-11 (CCl3F) and CFC-12 (CCl2F2), during the second half of the 20th century. It is important to continue monitoring the evolution of these source gases and reservoirs, in support of the Montreal Protocol and also indirectly of the Kyoto Protocol. The Atmospheric Ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 66 publications
10
76
0
Order By: Relevance
“…Mismatches are thus possible in terms of time and space. This result agrees with similar analyses made by Mahieu et al (2008), who show that there is ∼10-20 % ACE-FTS bias compared to HALOE for altitudes between 20 and 55 km. Work by Froidevaux et al (2008) also show that the biases between MLS and HALOE are of a similar magnitude in the same altitude region.…”
Section: Hclsupporting
confidence: 82%
See 1 more Smart Citation
“…Mismatches are thus possible in terms of time and space. This result agrees with similar analyses made by Mahieu et al (2008), who show that there is ∼10-20 % ACE-FTS bias compared to HALOE for altitudes between 20 and 55 km. Work by Froidevaux et al (2008) also show that the biases between MLS and HALOE are of a similar magnitude in the same altitude region.…”
Section: Hclsupporting
confidence: 82%
“…Currently, HCl v2.2 VMRs are from ∼10-50 km with a vertical resolution of approximately 3-4 km. Comparisons of ACE-FTS HCl to various other satellite and ground based instrumentation show that there is a good agreement of generally better than 5-10 % above 20 km (Mahieu et al, 2008). At present, no error analysis for ACE-FTS atmospheric products has been made.…”
Section: Ace-ftsmentioning
confidence: 99%
“…3.2, HALOE v19 HF has been validated against ACE-FTS v2.2, with the ACE measurements biased high by around 5-20 % between 15 and 49 km (Mahieu et al, 2008). Furthermore, HF data from the MkIV interferometer for three flights (2003)(2004)(2005) agree well with ACE-FTS, with relative differences above 19 km within ±10 %, suggesting that there is a low bias in HALOE.…”
Section: Haloesupporting
confidence: 49%
“…The ACE v2.2 HF data product, which uses a slightly different microwindow set from v3.0/v3.5 as well as an earlier version of the PT retrieval, has previously been validated, for example, against measurements taken by HALOE and the MkIV interferometer (Mahieu et al, 2008). It was found that ACE-FTS v2.2 HF measurements are biased high compared to HALOE, with mean differences around 5-20 % between 15 and 49 km.…”
Section: Ace-ftsmentioning
confidence: 99%
“…Tropospheric columns have been shown to represent the magnitude and seasonality of in situ measurements (Saad et al, 2014;Washenfelder et al, 2003;Wang et al, 2014). The tropospheric CH 4 column-averaged DMFs (X t CH 4 ) are derived by the hydrogen fluoride (HF) proxy method described in Saad et al (2014), which uses the relationship between CH 4 and HF in the stratosphere, derived from ACE-FTS satellite measurements (Bernath, 2005;De Mazière et al, 2008;Mahieu et al, 2008;Waymark et al, 2014), to calculate and remove the stratospheric contribution to X CH 4 . The X t CH 4 used in this analysis have been processed consistently with the GGG2014 TCCON products, with air-mass dependence and calibration factors calculated for and applied to X t CH 4 .…”
Section: Tropospheric Methane Columnsmentioning
confidence: 99%